Censorship detected in LY (Libya) - Voidly (2026)
CRITICAL severity censorship detected in Libya. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: LY-2026-0778
Keywords: censorship; LY; censorship; critical